HETEROTIC PERFORMANCE OF CMS BASED EXPERIMENTAL HYBRIDS OVER THE ENVIRONMENTS FOR YIELD, ITS ATTRIBUTING TRAITS AND OIL CONTENT IN SAFFLOWER (Carthamus tinctorius L.)2 - INDRAYANI H. THORAT; V.L. GAWANDE; R.D. RATNAPARKHI; N.S. RATHOD (The Bioscan, 2021)
Thirty hybrids, their parents along with two checks viz., PKV Pink and AKS 207 were evaluated in RBD with three replications and three environments to estimate heterosis for seed yield, its contributing traits and oil content. Highest heterosis over the best check was noted for number of branches per plant in cross AKS CMS 2A x BHIMA and useful heterosis for seed yield per plant in AKS CMS 2A x BHIMA. Significant and positive heterosis observed for majority of yield attributing traits viz., primary branches, capitula per plant, and 100 seeds weight over best check and it was recorded by hybrids AKS CMS 2A x BHIMA, AKS CMS 2A x GMU 3876, AKS CMS 2A x BHIMA, respectively. Further, hybrid AKS CMS 2A x BHIMA was found better than both checks for earliness. Among the 30 crosses, AKS CMS 2A x GMU 3876, AKS 2A x GMU 3863 and AKS 2A x BHIMA found to be promising on the basis of mean performance and heterotic response. These promising hybrids may be used for commercial cultivation after thorough multi-location testing and may also be effectively used for isolating transgressive segregants (by crossing B line of concerned CMS with same male parent).